Cardiovascular magnetic resonance evidence of myocardial fibrosis and its clinical significance in adolescent and adult patients with Ebstein’s anomaly - Yang, Dan (J Cardiovasc Magn Reson, 2018)
BACKGROUND: Myocardial fibrosis is a common pathophysiological process that is related to ventricular remodeling in congenital heart disease. However, the presence, characteristics, and clinical significance of myocardial fibrosis in Ebstein’s anomaly have not been fully investigated. This study aimed to evaluate myocardial fibrosis using cardiovascular magnetic resonance (CMR) late gadolinium enhancement (LGE) and T1 mapping techniques, and to explore the significance of myocardial fibrosis in adolescent and adult patients with Ebstein’s anomaly. METHODS: Forty-four consecutive patients with unrepaired Ebstein’s anomaly (34.0 ± 16.2 years; 18 males), and an equal number of age- and gender-matched controls, were included. A comprehensive CMR protocol consisted of cine, LGE, and T1 mapping by modified Look-Locker inversion recovery (MOLLI) sequences were performed. Ventricular functional parameters, native T1, extracellular volume (ECV), and LGE were analyzed. Associations between myocardial fibrosis and disease severity, ventricular function, and NYHA classification were analyzed. RESULTS: LGE was found in 10 (22.7%) patients. Typical LGE in Ebstein’s anomaly was located in the endocardium of the septum within the right ventricle (RV). The LV ECV of Ebstein’s anomaly were significantly higher than those of the controls (30.0 ± 3.8% vs. 25.3 ± 2.3%, P < 0.001). An increased ECV was found to be independent of the existence of LGE. Positive LGE or higher ECV (≥30%) was associated with larger fRV volume, aRV volume, increased disease severity, and worse NYHA functional class. In addition, ECV was significantly correlated with the LV ejection fraction (P <  0.001). CONCLUSIONS: Both focal and diffuse myocardial fibrosis were observed in adolescent and adult patients with Ebstein’s anomaly. Increased diffuse fibrosis is associated with worse LV function, increased Ebstein’s severity, and worse clinical status.